2023
DOI: 10.3390/ijerph20043108
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Earthworm (Dendrobaena veneta Rosa) Biomass Is Suitable as an Alternative Protein Source

Abstract: The selected chemical composition (dry matter, ash, total protein, and crude fat) of the integumentary muscles of Dendrobaena veneta were determined, plus the dry matter (DM) percentage content of 17 amino acids and the profile (%) of fatty acids. Results were compared with a more fully studied earthworm, Eisenia fetida. In addition, the composition of exogenous amino acids was compared to the WHO standard for pork, beef, and chicken eggs. Both earthworm species were grown on the same kitchen waste, and protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
4
6
3
Order By: Relevance
“…The table shows a high concentration of glycine, histidine, leucine, lysine, and glutamic acid. These results are similar to those reported by Garczyńska et al (2023) a study evaluating the nutritional composition of earthworms as a protein source [ 34 ]. Additionally, the presence of a high content of essential amino acids (EAA: 54 %) suggests the high nutritional value of this protein.…”
Section: Resultssupporting
confidence: 92%
“…The table shows a high concentration of glycine, histidine, leucine, lysine, and glutamic acid. These results are similar to those reported by Garczyńska et al (2023) a study evaluating the nutritional composition of earthworms as a protein source [ 34 ]. Additionally, the presence of a high content of essential amino acids (EAA: 54 %) suggests the high nutritional value of this protein.…”
Section: Resultssupporting
confidence: 92%
“…It can be observed that the paste has a high protein content compared to other macro compounds, which are mainly albumin, globulin, and glutelin. This protein concentration is within the normal range reported in the literature, which indicates that the earthworm has protein values greater than 60 % [ 33 , 34 ]. Regarding ash content, the values found were slightly higher than those reported by Garczyńska for the earthworm ( Dendrobaena veneta Rosa ); however, the fat content was significantly lower compared to theirs (12.21 %) [ 34 ].…”
Section: Results and Discusiónsupporting
confidence: 82%
“…This protein concentration is within the normal range reported in the literature, which indicates that the earthworm has protein values greater than 60 % [ 33 , 34 ]. Regarding ash content, the values found were slightly higher than those reported by Garczyńska for the earthworm ( Dendrobaena veneta Rosa ); however, the fat content was significantly lower compared to theirs (12.21 %) [ 34 ]. The high percentage of proteins of high biological value makes this substrate a viable alternative for biotechnological applications such as enzymatic hydrolysis [ 33 , 35 ].…”
Section: Results and Discusiónsupporting
confidence: 82%
“…Decanting the supernatant was carried out with care. Equation (13) was used to determine the ability to contain oil or water, expressed as mL•g −1 .…”
Section: Foaming Capacity and Stability Of Eappe Suspensionmentioning
confidence: 99%
“…As earthworms have a substantial protein content [5][6][7], earthworm protein is therefore being utilised as an ingredient in pelleted animal feeds in the United States, Canada, and Japan [8]. On a dry weight basis, earthworms are typically composed of 65% protein, 14% fat, 14% carbohydrate, and 3% ash [9][10][11][12][13]. It is reported that feed meals produced from earthworms can typically have a higher protein content and a nutritionally better amino acid composition than meals made from fish or soybeans [14].…”
Section: Introductionmentioning
confidence: 99%